Socio-economic impacts of development programs among the low-income households in Kelantan, Malaysia - Wan Nurulasiah Wan Mustapa (2019)
Malaysian development organisations offer a diversity of programmes to uplift the socio-economic condition of low-income households in Kelantan, Malaysia. This study examines the impacts of two initiatives which are access to micro-credit and enterprise development training program on households’ income, micro-enterprise income, micro-enterprise assets, and economic vulnerability among low-income households in Kelantan, Malaysia. By adopting a cross sectional design, the data were collected through random selection across participant lists of three development organisations which are AIM, TEKUN and LKIM. The total was 450 low-income households from seven districts in the state of Kelantan. The multiple regression analysis was used to analyse the data. The regression analysis shows that access to micro-credit and enterprise development training programmes have positive impact on households’ incomes, micro-enterprise incomes and micro-enterprise assets in order to decrease the level of economic vulnerability among the low-income households. This study extends the limited literature of household incomes, micro-enterprise incomes, microenterprise assets, economic vulnerability and extends the role of access to micro-credit and enterprise development training programmes, to provide new understanding on the impacts of contemporary development initiatives.